PENGARUH PASAR TIMAH INDONESIA (INATIN) TERHADAP POSISI TAWAR TIMAH INDONESIA - Nurtia, Nony Erau; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research explain about the effect of local tin market establishment by government to Indonesia’s bargaining position in trading. The market was listed on future market, ICDX (Indonesia Commodity and Derivatives Exchange) with code “INATIN” to set the global price benchmark by requiring the metal be traded on this local exchange before export. The purpose of this regulation to make Indonesia as the largest exporter and the second big producer of tin in the world, the place for international price discovery and lead a fair value of tin in order to give advantadge for Indonesia which before Indonesia followed the London Metal Exchange as a international metal market. ICDX helps Indonesia government perform monitoring to the trading activities, price movement, and all market data. As neo-mercantilsm paradigm, government role is needed to increas income and maximize the benefits through policy as an economic protection. This term expresses Keynes theory about the importance of government intervention controlling market. Keynes states that government role can not be separated in economic of country. According to the theory, in summary this research shows Indonesia has better bargaining position to rise the price and volume on local exchange, as the effect of Indonesia government intevention through regulation of export tin in Permendag 32/M-DAG/PER/6/2013. This result is evidenced in tin price increas and LME tin stock depression. The research illustrates the effect of government protection in trading as a part of economy politic international.Key words: Indonesia Tin Market, tin export policy, London Metal Exchange, protection